The role of semi-sports games in developing learning motivation for primary stage pupils from the teachers' point of view. - بوشيبة , مصطفى (Journal of Sport Science Technology and Physical Activities, 2021)
The study aims to identify the role of semi-sports games in developing learning motivation for primary school students from the teachers’ point of view. For this purpose, we used the descriptive approach on a sample of 64 teachers chosen randomly. To collect data, we used the learning motivation scale tool, and after collecting the results and treating them statistically It was concluded that the semi-sports games have a role in developing the learning motivation of primary school students from the teachers' point of view, and on this basis the study recommended relying on semi-sports games in the national education curriculum for primary education.